Appendage Regeneration After Autotomy is Mediated by Baboon in the Crayfish Procambarus Fallax F. Virginalis Martin, Dorn, Kawai, Heiden and Scholtz, 2010 (Decapoda: Astacoidea: Cambaridae). Issue 5 (1st September 2016) - Shinji, Junpei; Miyanishi, Hiroshi; Gotoh, Hiroki; Kaneko, Toyoji
Abstract: Autotomy is an adaptive response in which animals escape from predators by shedding their own appendages. It is made possible by the presence of an efficient mechanism for regeneration. Decapod crustaceans frequently exhibit excellent abilities to regenerate complete pereopods in just a few molts following autotomy. The molecular basis of regeneration pereopods in decapods remains unclear. We identified the primary structure of Baboon (Babo), a type I TGF - β superfamily receptor involved in the activin pathway, in the crayfish, Procambarus fallax f. virginalis Martin, Dorn, Kawai, Heiden and Scholtz, 2010 . Molecular cloning revealed that babo possesses three splice variants. The expression levels of the functional babo transcript did not show increases during regeneration. RNA interference (RNAi) targeting a common region of the babo sequence, however, caused a reduction in regenerated pereopod lengths. No loss or reduction in a specific article was observed. Instead, the regenerated legs were smaller but retained the morphology and proportions of regenerated legs from control animals. Babo thus appears to control the growth, but not the pattern, of legs during the regeneration process in decapod crustaceans.